A comparison of 4‐Fr with 5‐Fr endoscopic nasopancreatic drainage catheters: A randomized, controlled trial. Issue 10 (October 2016) - Mouri, Teruo; Sasaki, Tamito; Serikawa, Masahiro; Ishigaki, Takashi; Ishii, Yasutaka; Shimizu, Akinori; Tsuboi, Tomofumi; Kurihara, Keisuke; Tatsukawa, Yumiko; Miyaki, Eisuke; Kawamura, Ryota; Tsushima, Ken; et al.
Abstract: Background and Aim: Although endoscopic nasopancreatic drainage (ENPD) is useful for collecting samples for pancreatic juice cytology and for treating leakage of pancreatic juice and occlusive pancreatitis, placement of the ENPD catheter is associated with complications such as post‐endoscopic retrograde cholangiopancreatography pancreatitis (PEP). We investigated whether an ENPD catheter with a smaller diameter could reduce the incidence of complications. Methods: Patients requiring placement of an ENPD catheter ( n  = 254) were enrolled and randomly assigned to one of two catheter‐size groups: the 4‐Fr group or the 5‐Fr group. The incidence of PEP, cholangitis, and spontaneous catheter displacement and the suitability of pancreatic juice cytology samples were compared between groups. In addition, univariate and multivariate analyses were conducted on factors associated with PEP. Results: The incidence of PEP was significantly lower in the 4‐Fr group compared with the 5‐Fr group (4.1% vs 12.4%, respectively; P  = 0.021). The rate of cholangitis and spontaneous catheter displacement and the suitability of pancreatic juice cytology samples did not differ between groups. Multivariate analysis revealed that the risk of PEP was 3.7 times higher when using a 5‐Fr catheter than when using a 4‐Fr catheter ( P  = 0.019). In addition, the risk of PEP was 4.1 times higher in patients with an intraductal papillary mucinous neoplasm than in those without ( P  = 0.0049) and 4.6 times higher in patients aged <65 than in those aged ≥65 ( P  = 0.0033). Conclusions: A 4‐Fr catheter is as useful as a 5‐Fr catheter and is associated with a significantly lower incidence of PEP.